High maneuvering target tracking ATPM-IMM algorithm - Hao ZENG; Wangqiang MU; Shunping YANG (Tongxin xuebao)
For high maneuvering target tracking, the accuracy of tracking will degrade in common IMM algorithm due to the fixed transition probability matrix.Therefore, a new ATPM-IMM algorithm for high maneuvering target tracking was proposed, which could update the transition probability matrix adaptively.The proposed algorithm requires less prior information of model posterior probability and transition probability matrix, it is suitable for both high and weak maneuvering target tracking.Simulation results demonstrate that the filtering accuracy of the proposed algorithm is improved about 11% compared with the existing algorithms.